Hollywood on the Hudson : ﬁlm and television in New York from Grifﬁth to Sarnoff / Richard Koszarski. - Koszarski, Richard
In Hollywood on the Hudson, Richard Koszarski rewrites an important part of the history of American cinema. During the 1920s and 1930s, film industry executives had centralized the mass production of feature pictures in a series of gigantic film factories scattered across Southern California, while maintaining New York as the economic and administrative center. But as Koszarski reveals, many writers, producers, and directors also continued to work here, especially if their independent vision was too big for the Hollywood production line.